Comparing the agenda setting role of the Pakistani and Indian newspapers in disasters: a case study of the 2005 Kashmir earthquake - Gul, Shehla; Rahmann, Atta-Ur; Samiullah; Khan, Rafiq Ali (ERDKUNDE, 2020)
In the aftermath of the 2005 Kashmir earthquake, the media played a central role in linking victims to the government apparatus and the national and international community and highlighting weaknesses in the disaster management process. This study was conducted to analyze and compare the ‘agenda setting role’ of the Pakistani newspapers with that of the Indian newspapers after the 2005 Kashmir earthquake with a magnitude of 7.6 and resulting in over 78,000 fatalities in Azad Jammu & Kashmir, Khyber Pakhtunkhwa province of Pakistan and the Indian part of Kashmir. Two Pakistani and two Indian newspapers each with high circulation were selected for qualitative and quantitative analysis. A total of 630 articles were downloaded for analysis out of which 120 front page articles were finally analyzed with the help of five selected themes including extent of damage, phases of disaster, responsibility issues, types of framing and focus on disaster policies. The study revealed that there was a strong agenda setting role of both Pakistani and Indian newspapers in post 2005 Kashmir earthquake. The newspapers focused on broad policy issues using thematic framing techniques with a strong emphasis on response phase, whereas the least attention has been given to preparedness and mitigation strategies. The analysis further revealed that in both the countries, federal government was considered to be responsible for disaster management system by both Pakistani and Indian newspapers and the Indian newspapers have also strongly criticized the Indian army for their unsatisfactory emergency response operations. Newspapers are still one of the most important sources of information in many developing countries including Pakistan and India and they can play a positive role in the management of natural disasters by focusing on mitigation and preparation to prepare communities for future disasters.